THE EFFECT OF THE TRI HITA KARANA-ORIENTED PROBLEM-BASED LEARNING MODEL ON ECOLOGICAL ATTITUDES AND LEARNING OUTCOMES - Kade Dwi Suarni; I Wayan Gunartha; Dodi Sukmayadi (Indonesian Journal of Educational Development (IJED), 2023)
This study aims to determine the effect of the Tri Hita Karana-oriented problem-based learning model on ecological attitudes and science learning outcomes. The population in this study is 135 students, while the research sample is 61 students. The sampling technique uses cluster sampling and random sampling techniques. The data collection method in this study is the questionnaire method and the test method. Ecological attitude data are collected using a questionnaire instrument, while data on students' science learning outcomes are collected using a science learning achievement test. The data analysis technique used in this study is Manova. The results of the study are 1) there is a significant influence of the Tri Hita Karana-oriented problem pased learning model on ecological attitudes; 2) there is a significant influence of the Tri Hita Karana-oriented problem-based learning model on science learning outcomes; and 3) collectively there is a significant influence of the Tri Hita Karana-oriented problem-based learning model on ecological attitudes and science learning outcomes.